Fibronectin-binding protein of Streptococcus pyogenes: sequence of the binding domain involved in adherence of streptococci to epithelial cells. - Talay, S R (1992)
The sequence of the fibronectin-binding domain of the fibronectin-binding protein of Streptococcus pyogenes (Sfb protein) was determined, and its role in streptococcal adherence was investigated by use of an Sfb fusion protein in adherence studies. A 1-kb DNA fragment coding for the binding domain of Sfb protein was cloned into the expression vector pEX31 to produce an Sfb fusion protein consisting of the N-terminal part of MS2 polymerase and a C-terminal fragment of the streptococcal protein. Induction of the vector promoter resulted in hyperexpression of fibronectin-binding fusion protein in the cytoplasm of the recombinant Escherichia coli cells. Sequence determination of the cloned 1-kb fragment revealed an in-frame reading frame for a 268-amino-acid peptide composed of a 37-amino-acid sequence which is completely repeated three times and incompletely repeated a fourth time. Cloning of one repeat into pEX31 resulted in expression of small fusion peptides that show fibronectin-binding activity, indicating that one repeat contains at least one binding domain. Each repeat exhibits two charged domains and shows high homology with the 38-amino-acid D3 repeat of the fibronectin-binding protein of Staphylococcus aureus. Sequence comparison with other streptococcal ligand-binding surface proteins, including M protein, failed to reveal significant homology, which suggests that Sfb protein represents a novel type of functional protein in S. pyogenes. The Sfb fusion protein isolated from the cytoplasm of recombinant cells was purified by fast protein liquid chromatography. It showed a strong competitive inhibition of fibronectin binding to S. pyogenes and of the adherence of bacteria to cultured epithelial cells. In contrast, purified streptococcal lipoteichoic acid showed only a weak inhibition of fibronectin binding and streptococcal adherence. These results demonstrate that Sfb protein is directly involved in the fibronectin-mediated adherence of S. pyogenes to epithelial cells.